An Ophthalmologist's Insight Into The Viral Pandemics - Dhiman, Rebika (J Optom, 2022)
In recent past, major pandemics and epidemics have occurred due to the emergence and resurgence of the novel strains of viruses like Influenza [HINI-A “Spanish Flu”, H1N1-Novel A “Swine flu”], Corona [Middle East Respiratory Syndrome (MERS), Severe acute respiratory syndrome (SARS-CoV-1, SARS-CoV-2)] and Ebola virus [Ebola virus disease]. These infectious diseases may have several ocular manifestations and rarely might be the presenting symptom of the underlying disease. The eyes can act as a portal of entry and/or route of viral transmission for these pathogens. Therefore, an ophthalmologist/optometrist needs to act with ample preparedness and responsibility. Establishing a standard of care in ophthalmic practice by modifying the conventional examination techniques and adopting tele-ophthalmology model to triage the patients can control the community spread of the disease. This article aims to elucidate the ocular manifestations in these pandemics and measures that should be adopted in ophthalmic practice to prevent the disease transmission.